Building Sustainable Managerial Performance in Modern Organizations - Haryoto, Cecep Yoto (Ilomata International Journal of Management, 2026)
This study explains how perceived sustainability-oriented managerial performance is maintained in dynamic and digitalized workplaces by integrating strategic leadership, digital leadership capability, and perceived organizational support with two human-centered mechanisms. Sustainable managerial performance is defined and measured at the individual manager level as managers’ self-reported ability to sustain consistent, resilient, and adaptive performance over time through managerial actions in economic, environmental, and social domains within their area of responsibility. Survey data from 360 managers in Indonesia were analyzed using PLS-SEM to test direct effects and parallel mediation. The results show that strategic leadership, digital leadership capability, and perceived organizational support significantly strengthen manager well-being and managerial engagement, which in turn enhance sustainable managerial performance. In terms of magnitude, manager well-being is the stronger predictor of sustainable managerial performance compared with managerial engagement, indicating that psychological capacity is a more influential pathway than motivational involvement alone. Among the exogenous drivers, strategic leadership shows the largest direct contribution to sustainable managerial performance, followed by digital leadership capability and perceived organizational support. The parallel mediation pattern suggests that leadership and support sustain managerial performance simultaneously by improving well-being and reinforcing engagement rather than through a single sequential mechanism. These findings extend sustainable performance theory at the managerial level and imply that organizations should prioritize leadership development that strengthens strategic direction and digital readiness while implementing support practices that protect well-being and maintain engagement to sustain managerial effectiveness over time.